Pengaruh Model Pembelajaran Numbered Heads Together dan Motivasi Belajar Terhadap Hasil Belajar - ilham yuliady; Hendra Dani Saputra; Yogi Dian Alfana; A'yan Sabitah (AEEJ : Journal of Automotive Engineering and Vocational Education, 2023)
This research based on the problem of the learning process of the Engineering Mechanics course. The teacher center learning process causes students to be passive so that students feel bored because of one way communication. Based on data student learning outcomes, it is still not well achieved, therefore it is necessary to apply the numbered heads together learning model to improve learning motivation and learning outcomes. This type of reseach is a factorial 2x2. The subjects of this study were 48 students. The sampling technique is carried out random cluster sampling. Data collection by dissemination of learning motivation questionnaires and learning outcome test instruments and analyzed using two ways anova. Based on the results of data testing, it can be concluded that the Numbered heads together learning model can improve student motivation and learning outcomes. Penelitian ini dilatar belakangi permasalahan proses pembelajaran mata kuliah Mekanika Teknik. Proses pembelajaran yang terpusat pada dosen menyebabkan mahasiswa menjadi pasif sehingga mahasiswa merasa bosan karena komunikasi satu arah. Berdasarkan data hasil belajar mahasiswa masih belum tercapai dengan baik, maka dari itu perlu dilakukan penerapan model pembelajaran numbered heads together dalam peningkatan motivasi belajar dan hasil belajar. Jenis penelitian ini eksperimen dengan desain faktorial 2x2. Subjek penelitian ini mahasiswa yang berjumlah 48 orang. Teknik pengambilan sampel dilakukan random cluster sampling. Pengumpulan data dengan penyebaran angket motivasi belajar dan Instrumen tes hasil belajar dan dianalisa dengan two ways anova. Berdasarkan hasil pengujian data dapat disimpulkan bahwa model pembelajaran numbered heads together dapat meningkatkan motivasi belajar dan hasil belajar mahasiswa.